Design and implementation of smart traffic light controller using VHDL language - T. Gadawe, Nour; L. Qaddoori, Sahar (International Journal of Engineering and Technology, 2019)
The purpose of this paper is to design and implementation of smart traffic light controller system using VHDL language and FPGA. A structure of four road intersection has been selected. The intersection to be controlled is between a busy (main street), and somewhat less busy (side street), with sensor for the side street and walk request button. Also, the system contains switches to control the traffic light manually. The intersection uses four timing parameters with ability to change these parameters manually. The system has been successfully tested with VHDL using Xilinx ISE 14.7i software environment and Chip-Scope, while, it is implemented in hardware using Xilinx Spartan 3E FPGA. It is easy to use and the cost for the same is also less as compared to the others. The designed traffic light control system is presented to work correctly as predictable.